Trainers’ Attitudes towards Cardiopulmonary Resuscitation, Current Care Guidelines, and Training - M. Mäkinen; M. Castrén; J. Nurmi; L. Niemi-Murola (Emergency Medicine International)
Objectives. Studies have shown that healthcare personnel hesitate to perform defibrillation due to individual or organisational attitudes. We aimed to assess trainers’ attitudes towards cardiopulmonary resuscitation and defibrillation (CPR-D), Current Care Guidelines, and associated training. Methods. A questionnaire was distributed to CPR trainers attending seminars in Finland (N=185) focusing on the updated national Current Care Guidelines 2011. The questions were answered using Likert scale (1 = totally disagree, 7 = totally agree). Factor loading of the questionnaire was made using maximum likelihood analysis and varimax rotation. Seven scales were constructed (Hesitation, Nurse’s Role, Nontechnical Skill, Usefulness, Restrictions, Personal, and Organisation). Cronbach’s alphas were 0.92–0.51. Statistics were Student’s t-test, ANOVA, stepwise regression analysis, and Pearson Correlation. Results. The questionnaire was returned by 124/185, 67% CPR trainers, of whom two-thirds felt that their undergraduate training in CPR-D had not been adequate. Satisfaction with undergraduate defibrillation training correlated with the Nontechnical Skills scale (p<0.01). Participants scoring high on Hesitation scale (p<0.01) were less confident about their Nurse’s Role (p<0.01) and Nontechnical Skills (p<0.01). Conclusion. Quality of undergraduate education affects the work of CPR trainers and some feel uncertain of defibrillation. The train-the-trainers courses and undergraduate medical education should focus more on practical scenarios with defibrillators and nontechnical skills.